Anti-gout potential of selected edible flowers - M. F. Abu Bakar (2024)
Gout is a form of inflammatory arthritis triggered by the interaction between monosodium urate crystals and tissues during the purine metabolism by xanthine oxidase. This study aimed to determine the xanthine oxidase inhibitory activity, total phenolic content, total flavonoid content and total anthocyanin content of 10 selected edible flowers, namely Rosa sp., Malus sp., Lavandula sp., Lilium sp., Hibiscus sabdariffa L., Chrysanthemum sp., Matricaria sp., Gomphrena sp., Myosotis sp. and Jasminum sp. extracted using hot water infusion method. Phytochemical contents and the anti-gout activity of the flower extracts using the xanthine oxidase inhibition assay were determined spectrophotometrically. The results revealed that three aqueous flower extracts (Rosa sp., Hibiscus sabdariffa L. and Malus sp.) exhibited potent xanthine oxidase inhibitory activity (IC₅₀ values, 0.10±0.15 µg/mL, 0.12±0.11 µg/mL and 2.59±3.8 µg/mL, respectively), which were comparable to the positive control, allopurinol (IC₅₀ value, 4.9±0.00 µg/mL). The highest phenolic and flavonoid contents were found in Lavandula sp. (4.39±0.13 mg GAE/g and 63.46±1.07 mg RE/g) while Rosa sp. showed the highest content of anthocyanin (70.14±4.82 mg c-3-gE/g). Positive correlations were observed between the phytochemicals and xanthine oxidase inhibitory activity of the flower extracts. Hence, this study suggests that Rosa sp., Hibiscus sabdariffa L. and Malus sp. possess anti-gout potential, which is associated with the presence of possible anti-gout phytochemicals. The isolation of the bioactive compounds that exhibit significant anti-gout activity among the selected flowers is recommended for future research.